Manajemen Kualitas Kerja Layanan: (Studi Kasus Gembleng Restaurant) - Ayu Lestari, Ni Kadek; Winda Yanti, Ni Kadek (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the partial and simultaneous influence of organizational culture, workload, and employee retention on work quality. The sample in this study was 35 employees of Gembleng Restaurant. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F-Test, and t-Test. The results showed that organizational culture has a positive and significant effect on work quality, workload has a positive and significant effect on work quality, and employee retention has a positive and significant effect on work quality. The researcher's suggestion is that Gembleng Restaurant should always supervise employees at work, so that employees will recheck the details of the work before handing it over. They should evaluate the amount of work given to employees so that they can assign work according to their abilities. They should create a bonus or incentive policy based on the performance achieved by employees. They should also pay attention to my health at work by providing adequate rest areas and providing adequate first aid.